Прогнозування та профілактика інтраопераційних ускладнень під час виконання однопортової холецистектомії при гострому холециститі - Клименко, Володимир Микитович; Кравченко, Борис Сергійович; Захарчук, Олександр Валентинович; Кравченко, Сергій Михайлович; Сиволап, Дмитро Віталійович; Клименко, В. Н.; Кравченко, Б. С.; Захарчук, А. В.; Кравченко, С. М.; Сиволап, Д. В.; Klimenko, V. M.; Kravchenko, B. S.; et al. (My University, 2015)
Лапароскопическая холецистэктомия (ЛХЭ) — это стандарт лечения желчнокаменной болезни. Однако при остром холецистите ЛХЭ приводит к росту частоты билиарных повреждений по сравнению с открытой техникой в 1,2–2 раза. Не определено место однопортового хирургического доступа при лечении острого холецистита. В представленной работе, согласно данным дооперационного УЗИ, времени до момента операции, морфологической формы острого холецистита, разработаны критерии, позволяющие прогнозировать эффективность выполнения однопортовой холецистэктомии, использования дополнительного троакарного доступа. Показана необходимость планирования стандартной ЛХЕ или минилапаротомии с целью профилактики интраоперационных осложнений холецистэктомии при остром холецистите. Actuality. Laparoscopic cholecystectomy (LCE) is the standard treatment of cholelithiasis. Acute cholecystitis increased incidence of biliary lesions during LCE as compared with the open technique in 1.2–2 times. There is no definition for single-port laparoscopic accesses for acute cholecystitis at present time. Goal. Determination of the criteria for selecting patients, the timing of operation, prognostic factors increase access while performing single-port laparoscopic cholecystectomy and depending on the data ultrasonography, time of onset in patients with acute cholecystitis. Materials and methods. The analysis of the performance of 52 cholecystectomy for acute cholecystitis through a transumbilical single-port laparoscopic access (SILS). Results. For preoperative ultrasound isolated 3 groups of patients. Group 1: bladder wall thickness of 3 mm and a length of 60 mm bladder, planned SILS access. 2nd group: bladder wall thickness to 4–8 mm and a length of 60–80 mm bladder, planned SILS access with optional additional trocar or conversion to standard laparoscopic. 3rd group: bladder wall thickness more than 8 mm and a length more than 80 mm bladder — perfomed diagnostic laparoscopy through the SILS access to estimations of conversion necessity to standard LCE or minimal laparotomic access. Group 1 — SILS-cholecystectomy (catarrhal form, since disease up to 24 hours) — 13 patients, two-additional 5-mm port in the right upper quadrant — SILS “plus”. Group 2 (phlegmon form, up to 48 hrs) — SILScholecystectomy — 20 patients, 6 — SILS “plus”, in 3 — conversion to laparoscopic cholecystectomy. In the third group (6 patients, phlegmon and gangrene form, up to 72 hrs) isolated SILS was impossible. Conclusions. Single-port cholecystectomy surgery is effective in acute cholecystitis taking into account the proposed criteria.
Прогнозирование и профилактика интраоперационных осложнений во время выполнения однопортовой холецистэктомии при остром холецистите
Prediction and prevention of intraoperative complications during performing single-port cholecystectomy for acute cholecystitis
Keywords: острый холецистит; однопортовая холецистэктомия; прогностические критерии; конверсия доступа; acute cholecystitis; single-port cholecystectomy; prognostic criteria for conversion of access